Sistem Pakar Diagnosa Hama Padi Menggunakan Metode Forward Chaining dan Backward Chaining - Wahyu Nugroho; Sumirah Sumirah; Rachmat Wahid Saleh Insani; Syarifah Putri Agustini Alkadri (Universitas Islam Lamongan, 2022)
Indonesian is the third largest country that produced rice in the world with yield result 54,65 billion ton grinding dry grain. Rice is the primary food for people in indonesian. the main problem that can reduce yield result is pest and disease that attack rice plant. the main purpose of this research is build an application expert system based on web with forward chaining and backward chaining methode to help farmers handle pest and disease problem that attack rice plant, forward chaining methode in this application is used to know what kind pest and disease that attack rice plant, and backward chaining methode is used to know what kind of action if pest and disease attack rice plant. the research result is this application can get 88,5% accuration, from the accuration in this application can get declared succed and can be use by farmer.